If every fifth physician is affected by burnout, what about the other four?: resilience strategies of experienced physicians - Zwack, Julika; Schweitzer, Jochen (Academic medicine, 2013)
Purpose - To identify health-promoting strategies employed by experienced physicians in order to define prototypical resilience processes and key aspects of resilience-fostering preventive actions. - Method - From January 2010 to March 2011, the authors conducted 200 semistructured interviews with physicians of different ages, disciplines, and hierarchical status from across Germany. The interview transcripts were analyzed according to the Content Analysis method. - Results - Analysis revealed 30 subcodes in three dimensions: (1) job-related gratifications derived from treatment interactions, (2) practices, such as leisure-time activities, self-demarcation, limitation of working hours, and continuous professional development, and (3) attitudes, such as acceptance of professional and personal boundaries, a focus on positive aspects of work, and personal reflexivity. - Conclusions - The reported strategies and attitudes helped to develop mental, physical, and social resource pools that fostered effective decision making. Successful coping, in turn, encouraged the maintenance of resilience-promoting abilities. In relation to Conservation of Resources Theory, physician resilience emerged as the ability to invest personal resources in a way that initiates positive resource spirals in spite of stressful working conditions. Enriching traditional stress management approaches with the dynamic of positive as well as negative resource spirals would thus appear to be a promising approach.